2024
DOI: 10.1039/d3ta05397k
|View full text |Cite
|
Sign up to set email alerts
|

The role of protein folding in prenucleation clusters on the activity of enzyme@metal–organic frameworks

Brooke P. Carpenter,
Ben Rose,
Elisa M. Olivas
et al.

Abstract: Two steps must be satisfied to achieve high activity enzyme@MOFs: proper enzyme folding and low MOF crystallinity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…15−17 In addition, some amorphous MOFs, such as Zn-based metal azolate coordination polymer (ZnCP) synthesized using Zn 2+ 3-methyl-1,2,4-triazolate (3-MTZ) at a low ratio of organic ligand to metal ion, 18 exhibited better catalytic performance than the traditional MOFs like ZIF-8, owing to the large defects and interconnected mesopores allowing the substrate to access the inside of immobilized enzymes, and the compatibility and "armor-like" effect beneficial for the preservation of the entrapped enzymes under extreme conditions. 19,20 Moreover, introducing polymers into MOFs was proved to enhance the catalytic performance of MOF-immobilized enzymes by creating mesopores inside MOFs via competitive coordination or serving as a protective layer to reduce the influence of unfavorable interfacial interactions on enzyme conformations. 21,22 Furthermore, several research groups have revealed that the introduction of amino acids within MOFs could greatly improve the properties of MOF-immobilized enzymes by inducing an active enzyme conformation, 23,24 accelerating the encapsulation process, 25,26 or changing the morphology of MOFs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15−17 In addition, some amorphous MOFs, such as Zn-based metal azolate coordination polymer (ZnCP) synthesized using Zn 2+ 3-methyl-1,2,4-triazolate (3-MTZ) at a low ratio of organic ligand to metal ion, 18 exhibited better catalytic performance than the traditional MOFs like ZIF-8, owing to the large defects and interconnected mesopores allowing the substrate to access the inside of immobilized enzymes, and the compatibility and "armor-like" effect beneficial for the preservation of the entrapped enzymes under extreme conditions. 19,20 Moreover, introducing polymers into MOFs was proved to enhance the catalytic performance of MOF-immobilized enzymes by creating mesopores inside MOFs via competitive coordination or serving as a protective layer to reduce the influence of unfavorable interfacial interactions on enzyme conformations. 21,22 Furthermore, several research groups have revealed that the introduction of amino acids within MOFs could greatly improve the properties of MOF-immobilized enzymes by inducing an active enzyme conformation, 23,24 accelerating the encapsulation process, 25,26 or changing the morphology of MOFs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As one of the most widely explored MOFs for enzyme immobilization, zeolitic imidazolate framework-8 (ZIF-8) can be synthesized using Zn 2+ and 2-methylimidazole ligand (2-MI) under biologically compatible conditions . However, the high hydrophobicity of ZIF-8 can give rise to strong hydrophobic interactions with proteins, which often engender conformational changes that denature the proteins and lead to the loss of activity. , In recent years, more hydrophilic ZIF materials like ZIF-90 and metal azolate framework-7 (MAF-7) have been reported to be more compatible with enzymes for more retention of catalytic activity. In addition, some amorphous MOFs, such as Zn-based metal azolate coordination polymer (ZnCP) synthesized using Zn 2+ and hydrophilic 3-methyl-1,2,4-triazolate (3-MTZ) at a low ratio of organic ligand to metal ion, exhibited better catalytic performance than the traditional MOFs like ZIF-8, owing to the large defects and interconnected mesopores allowing the substrate to access the inside of immobilized enzymes, and the compatibility and “armor-like” effect beneficial for the preservation of the entrapped enzymes under extreme conditions. , …”
Section: Introductionmentioning
confidence: 99%
“…MNs exhibit an extraordinary swelling characteristic (>500%), and the mechanical strength slightly increased to 0.25 N/needle . However, such modifications usually can be achieved under strict conditions, such as high temperatures (∼80 °C) and organic solvents, which could generally impact the implanted enzyme-based catalyst system of MNs. , Notably, these methods usually raise safety concerns during application, especially in fruit and food diagnostics, which require further biocompatibility amendment of the SF β -sheet formation to fit the hardness and swelling used in the diagnostic.…”
Section: Introductionmentioning
confidence: 99%